Dynamics of droplets and bubbles coated with magnetic particles - Zhao, Xue (2009)
Based on the interfacial self-assembly of magnetic nanometer and micrometer sized particles, we demonstrate the formation of microspheres covered by magnetic nanoparticles, millimeter-sized oil droplets stabilized by a layer of closely-packed microparticles, and a new type of bubble with a permanent magnetization. The motion of individual magnetic microspheres in a defined magnetic field gradient is investigated and the susceptibilities of individual magnetic microspheres are estimated. Our measurement shows that the magnetic moment of the microspheres scales with their diameters. This is reasonable since the magnetic nanoparticles are attached to the surface of these microspheres, which means the larger the surface area, the more possibilities for these magnetic nanoparticles to attach to the surface.